A SYSTEMATIC REVIEW OF AUGMENTED REALITY’S IMPACTS ON EDUCATION - Rinaldo Pardomuan Sinaga,; Rizki Hikmawan, (ENGLISH JOURNAL, 2025)
Augmented Reality (AR) has significant potential to enhance education by providing immersive and interactive learning experiences. This study conducts a Systematic Literature Review (SLR) to explore the challenges and opportunities in AR implementation for education. Findings indicate that while AR improves student engagement and comprehension of abstract concepts, its adoption in developing countries is hindered by limited infrastructure, inadequate teacher training, and unsupportive policies. In contrast, developed nations have successfully integrated AR due to stronger infrastructure, comprehensive educator training, and supportive policies. To facilitate AR adoption in developing countries, investments in infrastructure, teacher capacity-building, and policy support are essential. These findings highlight the need for collaboration among governments, educators, and technology developers to address challenges and expand access to AR-enhanced education.